Pengembangan Hypothetical Learning Trajectory Materi Perkalian Bentuk Aljabar Kelas VII dengan Pendekatan Realistic Mathematics Education - Yuliani, Salsa Bella; Palupi, Evangelista Lus Windyana; Fiangga, Shofan (Universitas Negeri Surabaya, 2024)
The Hypothetical Learning Trajectory (HLT) has a role in constructing potential learning paths for students based on their thinking. It includes learning objectives, learning activities, and learning hypotheses to help students reach the desired endpoint. Therefore, this research aims to produce a learning trajectory for algebraic multiplication using the Realistic Mathematics Education (RME) approach. The method used is design research, consisting of three stages: Preparing for the Experiment, Design Experiment, and Retrospective Analysis. The HLT design was tested on 6 participants selected based on the lowest scores on a pre-test. This research was conducted up to the pilot experiment stage with five activities aimed at learning objectives, including the multiplication of forms or for activity 1, the multiplication of forms for activity 2, the multiplication of forms or for activity 3, the multiplication of forms or for activity 4, and the multiplication of forms for activity 5. Video recordings, field notes, documentation of student work, and pre-test and post-test data were collected in this study. The results of this study indicate that HLT design 1, which emerged from the design implementation, can help students learn algebraic multiplication. Meaningful contexts for students, combined with questions posed by the teacher, encourage students to think about the mathematical ideas discussed, thereby generating different strategies for solving given problems. Keywords: HLT, RME, Design Research, Algebraic Multiplication